Regional odontodysplasia accompanied by hypodontia: a case report and literature review - ZHANG Beibei, HUANG Yongqing, DUAN Xiaohong (口腔疾病防治, 2025)
Objective To explore the clinical and imaging characteristics of patients with regional odontodysplasia accompanied by hypodontia and to provide a reference for clinical diagnosis and treatment. Methods This report presents the imaging manifestations, diagnosis, and treatment of a case of regional odontodysplasia (RO) accompanied by hypodontia. It includes a retrospective summary of the dynamic changes in the imaging characteristics of the affected teeth over a 5-year period, along with a comparative analysis of the literature. The patient was a 9-year-old female who presented to the Clinic of Oral Rare and Genetic Diseases of our hospital with the chief complaint of “discomfort for over seven months following the extraction of the teeth in the left mandibular region.” Based on her clinical manifestations and imaging findings, she was diagnosed with RO in the left mandible and with hypodontia of permanent teeth 12 and 34. A treatment plan was formulated, and long-term follow-up was conducted. The current radiographic images were compared with previous imaging data to summarize the developmental changes in her teeth, and a comparative analysis was also performed with the literature to identify similarities and differences with previously reported RO dental characteristics. Results During the follow-up period, the patient's symptoms did not worsen, and a conservative observation approach was adopted; the treatment plan was decided after the eruption of the affected teeth. By comparing and analyzing imaging data from three ages (4.5, 8.5, and 9 years old), it was determined that the deciduous and permanent teeth in the left mandible of this patient exhibited typical “ghost” radiographic features, alongside hypodontia of teeth 12 and 34, as well as the delayed development of tooth 35. A literature review and analysis indicated that RO manifests clinical characteristics such as delayed tooth eruption, reduced tooth size, and yellow crowns, along with typical “ghost” radiographic appearances. Treatment requires a personalized approach based on the patient’s specific condition. To date, only five cases of RO patients with hypodontia have been reported, while the delayed development of permanent tooth buds has not yet been documented. Conclusion For patients with RO, dynamic imaging evaluation plays a critical role in early diagnosis. RO is associated with hypodontia and delayed tooth germ development. Long-term follow-up and personalized treatment plans are the key to RO treatment.